CATATROPIS SP. (TREMATODA: NOTOCOTYLIDAE) FROM THE BLACK COOT, FULICA ATRA LINNAEUS, 1758 (GRUIFORMES: RALLIDAE) IN SINDH PROVINCE OF PAKISTAN - N. A. Birmani; A. M. Dharejo; M. M. Khan. (Journal of Animal and Plant Sciences, 2011)
During present study on the helminth parasites of Black Coot, Fulica atra Linnaeus, 1758 (Gruiformes: Rallidae) in Sindh Province of Pakistan, two trematodes of the genus Catatropis Odhner, 1905 were recovered from intestine of host bird. The detailed study of the worms resulted the lack of some diagnostic characteristics for the identification up to the species level. Therefore, these worms are identified up to the generic level. Previously there is no record of the genus Catatropis Odhner, 1905 in the avian host of Pakistan.
Keywords: Avian trematode; Catatropis sp.; Fulica atra; Sindh; Pakistan.